2005
DOI: 10.1016/j.ijgo.2005.04.018
|View full text |Cite
|
Sign up to set email alerts
|

Plasma nitric oxide, endothelin-1 and urinary nitric oxide and cyclic guanosine monophosphate levels in hypertensive pregnant women

Abstract: The imbalance between NO and ET-1 may play a significant role in the pathophysiology of preeclampsia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 24 publications
3
34
2
Order By: Relevance
“…Moreover, WT sFlt-1 mice treated with ET-1 develop renal phenotypes similar to eNOS 2/2 sFlt-1 mice, evidenced by more severe albuminuria, decreased CCr, severe endotheliosis, and foot process effacement (Supplemental Figures S1 and S2). Our results are consistent with studies showing the association of ET-1 with pre-eclampsia [17][18][19] and with a recent study showing that sFlt-1 increases ET-1 expression in glomerular endothelial cells, 26 that ET-1 binds to its receptor in podocytes and causes nephrin shedding and proteinuria, and that an ET A receptor antagonist N-acetyl-[D-TRP 16 ]-ET1 fragment 16-21 abolishes these serial effects. 26 Taken together, our results indicate that the activated ET system is responsible for pre-eclampsia-like phenotypes observed in WT sFlt-1 and eNOS 2/2 sFlt-1 mice.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Moreover, WT sFlt-1 mice treated with ET-1 develop renal phenotypes similar to eNOS 2/2 sFlt-1 mice, evidenced by more severe albuminuria, decreased CCr, severe endotheliosis, and foot process effacement (Supplemental Figures S1 and S2). Our results are consistent with studies showing the association of ET-1 with pre-eclampsia [17][18][19] and with a recent study showing that sFlt-1 increases ET-1 expression in glomerular endothelial cells, 26 that ET-1 binds to its receptor in podocytes and causes nephrin shedding and proteinuria, and that an ET A receptor antagonist N-acetyl-[D-TRP 16 ]-ET1 fragment 16-21 abolishes these serial effects. 26 Taken together, our results indicate that the activated ET system is responsible for pre-eclampsia-like phenotypes observed in WT sFlt-1 and eNOS 2/2 sFlt-1 mice.…”
Section: Discussionsupporting
confidence: 92%
“…ET-1 is one of the most potent vasoconstrictors and is associated with pre-eclampsia. [17][18][19] sFlt-1 and lack of eNOS both increase the expression of preproET-1 and ET A R in the kidney, and eNOS 2/2 sFlt-1 mice have the highest expression of these (Figure 4). A selective ET A R antagonist ambrisentan abolished about two-thirds of elevated BP by sFlt-1 in both WT and eNOS 2/2 mice, indicating that ET plays a major role in increases in BP of pre-eclampsia ( Figure 5A), but that the difference in BP between WT and eNOS 2/2 mice is ET independent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study suggested that ET-1 plays an essential role in the failure of trophoblast invasion in the early stages of preeclampsia (12). Another study indicated that the level of circulating ET-1 correlates with the severity of the disease symptoms (4). Coincidental with the increase in circulating ET-1, Nishikawa et al reported a significant negative correlation between ET-1 levels and levels of the vasodilators NO and cGMP in preeclamptic women (24).…”
Section: Discussionmentioning
confidence: 98%
“…In literature, a large number of studies describing changes in endothelial function markers in PE can be found, in particular, an increase of plasma endothelin-1 (Baksu et al, 2005a;Bernardi et al, 2008a), soluble vascular cell adhesion molecule (sVCAM), plasma fibronectin (Aydin et al, 2006;Dane et al, 2009) and tissue fibronectin (Powers et al, 2008), a decrease of plasma and urinary nitric oxide (NO) levels (Baksu et al, 2005a;Mao et al, 2009).…”
Section: Endothelial Dysfunctionmentioning
confidence: 99%